The steppe tradition in international relations Russians, Turks and European state building 4000 BCE–2018 CE - Neumann, Iver B. 1959-; Wigen, Einar 1981- (Cambridge University Press, 2018)
Neumann and Wigen counter Euro-centrism in the study of international relations by providing a full account of political organisation in the Eurasian steppe from the fourth millennium BCE up until the present day. Drawing on a wide range of archaeological and historical secondary sources, alongside social theory, they discuss the pre-history, history and effect of what they name the 'steppe tradition'. Writing from an International Relations perspective, the authors give a full treatment of the steppe tradition's role in early European state formation, as well as explaining how politics in states like Turkey and Russia can be understood as hybridising the steppe tradition with an increasingly dominant European tradition. They show how the steppe tradition's ideas of political leadership, legitimacy and concepts of succession politics can help us to understand the policies and behaviour of such leaders as Putin in Russia and Erdogan in Turkey
Title from publisher's bibliographic system (viewed on 28 Jun 2018)
Keywords: Geschichte 4000 v. Chr.-2018; Asia, Central / History; Steppe; Nomade; Politische Kultur; Politisches System; Herrschaft; Eurasien; Russland; Türkei